2012
DOI: 10.1021/ja211272v
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Enantioselective Intramolecular Alkene Amination/Intermolecular Heck-Type Coupling Cascade

Abstract: Enantioselective copper-catalyzed cycliza-tion of γ-alkenylsulfonamides and a δ-alkenylsulfonamide in the presence of a range of vinyl arenes results in variously functionalized 2-substituted chiral nitrogen heterocycles via a formal alkene C–H functionalization process. Application of this reaction to the concise synthesis of a 5-HT7 receptor antagonist is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 180 publications
(76 citation statements)
references
References 48 publications
1
74
0
1
Order By: Relevance
“…In the context of copper-catalyzed heterocycle synthesis, we have explored both doubly intramolecular 4851 and intra-/intermolecular 52 carboamination approaches.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of copper-catalyzed heterocycle synthesis, we have explored both doubly intramolecular 4851 and intra-/intermolecular 52 carboamination approaches.…”
Section: Resultsmentioning
confidence: 99%
“…10a Sulfonamides 6a and 6b were synthesized as previously reported. 10,27 Characterization data for pyrrolidine 7a has been reported. 10a The synthesis of sulfonamide 6-[D] and the characterization data for indolines 7-[D] have been reported.…”
Section: Methodsmentioning
confidence: 99%
“…In 2012, Chemler and co-workers reported that a chiral b-aminoalkyl radical could be generated from an enantioselective aminocupration of a g-aminoalkene followed by C-Cu(II) homolysis (Scheme 17). 22 The generated radical could undergo direct alkenylation under oxidative conditions. Cu(OTf) 2 in combination with a chiral bisoxazoline was applied as the catalyst system and MnO 2 was used as the oxidant.…”
Section: Scheme 14mentioning
confidence: 99%